2016
DOI: 10.1021/acscatal.6b01068
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the P450-Catalyzed Oxidative Cyclization in the Biosynthesis of Griseofulvin

Abstract: Griseofulvin is an anti-fungal agent which has recently been determined to have potential anti-viral and anti-cancer applications. The role of specific enzymes involved in the biosynthesis of this natural product has previously been determined, but the mechanism by which a p450, GsfF, catalyzes the key oxidative cyclization of griseophenone B remains unknown. Using density functional theory (DFT), we have determined the mechanism of this oxidation that forms the oxa-spiro core of griseofulvin. Computations sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 44 publications
4
49
0
2
Order By: Relevance
“…376 (In passing we note this oxygen-independent route to spirocycles differs from the O 2 -dependent routes, e.g. to griseofulvin (Scheme 25) 136,137 , reflecting independent routes to this geometry-imposing bicyclic unit. ).…”
Section: Concluding Thoughtsmentioning
confidence: 92%
See 1 more Smart Citation
“…376 (In passing we note this oxygen-independent route to spirocycles differs from the O 2 -dependent routes, e.g. to griseofulvin (Scheme 25) 136,137 , reflecting independent routes to this geometry-imposing bicyclic unit. ).…”
Section: Concluding Thoughtsmentioning
confidence: 92%
“…The C-O coupling step was studied computationally by Grandner et al, in which they concluded a third, mechanism A, is the most likely and energetically favorable. 137 This is the radical addition mechanism in which the enzyme performs the O-H abstraction on B ring to give 140 , but avoids diradical formation. Direct attack of the phenoxy radical on A ring leads to ring closure and intermediate 141 , subsequent phenolic O-H abstraction by the heme affords 145 .…”
Section: Radical Cyclization Mechanismsmentioning
confidence: 99%
“…A similar coupling mechanism was computationally proposed for the P450 in the griseofulvin pathway. 15 …”
mentioning
confidence: 99%
“…However, the successful conversion of non‐spiro derivatives into spiro compounds led us to search for the deschlorinated spiro compounds ( 25 – 27 , and 28 – 30 ), which were indeed observed in wild‐type and Δ ams16 mutant strains, respectively (Figures S15 and S17). Previously, spiro‐forming enzymes were reported to be involved in the biosynthesis of natural products such as griseofulvin and pyrroindomycins (details about other compounds can be found in Tang et al …”
Section: Methodsmentioning
confidence: 99%